Developing a Growth Mindset through outdoor personal development: can an intervention underpinned by psychology increase the impact of an outdoor learning course for young people?. Issue 2 (3rd April 2017) - O'Brien, Kate; Lomas, Tim
ABSTRACT: This study considers the impact of using a series of Mindset interventions during a five-day outdoor personal development (OPD) course. Self-efficacy, resilience and Mindset were measured pre course, post course and one month post course. It was hypothesised that both experimental and control groups would increase their self-efficacy and resilience, and that the Mindset (experimental) group would significantly increase beyond the levels of the control group, who took part in the standard OPD course. It was also predicted that the Mindset group would move towards a Growth Mindset, whereas the control group would not show any change in Mindset. Hypotheses were tested using a randomised, quasi-experimental method. Separate mixed analyses of variance were carried out for each dependent variable, followed by planned comparisons and post-hoc tests using a Bonferroni correction. Results showed that both groups increased self-efficacy over time; however, there was no further significance for the experimental group. Resilience only increased significantly in the experimental group while the control group made no significant gain, and students in the experimental group moved significantly towards a Growth Mindset while the control group did not.